Transnational Social Capital, Business Model Design, and Firm's Growth in the Context of University Spin-off Companies - Yasin, Norazlina Mohd; Quoquab, Farzana; Kamarudin, Suzilawati (International Review of Management and Marketing, 2016)
The literature on the firm growth among University Spin-off Company has been widely studied in the strategic management literature and the technology transfer practice over the last 15 years. While many studies put emphasis on the firm's resources, yet how firm growth can be achieved under resource constraint is relatively under-explored. Therefore, through a conceptual model, it is argued that transnational social capital as firm's internal resources and business model design as firm's strategy can facilitate firm's growth under resource constraint. The study attempts to explore the extent to which the transnational social capital and business model design impact firm's growth under resource constraint. The theoretical framework utilised for this study is the extended form of resource-based view. The study postulates that internal resources that are available in young firms, function as antecedents of firm's growth. Malaysia is nominated as the context to investigate the accuracy of the proposed model with the focus on the university spin-off companies. This paper provides insight and understanding of transnational social capital, business model design, and firm growth among University Spin-off Company. Keywords: Transnational Social Capital; Business Model Design; Firm Growth; University Spin-off Company JEL Classifications: L2